Pengaruh Likuiditas Dan Solvabilitas Terhadap Harga Saham Pada PT Martina Berto Tbk - Nurwita (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to determine the effect of liquidity on stock prices, the effect of solvency on stock prices, and the joint effect of liquidity and solvency on stock prices at PT Martina Berto, Tbk, in 2010-2020. The research method uses quantitative and tests the classical assumptions and analyzes data including regression equations, coefficients of determination and hypothesis testing (t and f). The results showed that there was no significant influence and the ratio of liquidity as a variable (X1) on stock prices at PT. Martina Berto, Tbk in 2010-2020, there is significant influence and solvency as a variable (X2) on stock prices at PT. Martina Berto, Tbk in the 2010-2020 period. And there is a simultaneous and significant influence on Liquidity and Solvability on Share Prices at PT. Martina Berto, Tbk in the 2010-2020 period.